COVID-19 associated pulmonary aspergillosis-an unusual manifestation of COVID-19 - Anusuya, B.; Yamini, J. (International Journal of Advances in Medicine, 2023)
A recently identified condition known as COVID-19-associated pulmonary aspergillosis (CAPA) is connected to the COVID-19 pandemic and is known as post-COVID complications. More data are awaited, and a consensus criterion was recently published in an effort to spur more research and registries to assist clinical decision-making. However, it is evident that CAPA imposes a COVID-19 illness course that worsens with increased morbidity and mortality. Here we present the case of a 53-year-old male patient admitted to our hospital after recovering from COVID-19. Due to his clinical condition, some investigation criteria were performed and Aspergillus fumigatus was identified in his culture test. Treatment was provided with posaconazole as a first-line drug, and the patient showed a good clinical outcome.